Politeness Strategies in Sule’s Podcast - Bambang Panca Syahputra; Mitha Hartati; Yusni Khairul Amri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This study aims to examine the kind of politeness strategies used by Sule in his podcats with Rizky Febian, and the reason factors influence for using the politeness strategies. This study belongs to descriptive qualitative research. The data were gained by transcribing the whole utterances realized during the podcast. Then, the data were eliminated and sorted. Only Sule and Rizky Febian utterances were analyzes, encoded, described, and displayed in a discussion. There are four politeness strategies used by Sule. They are bald on record politeness strategy, positive politeness strategy, negative politeness strategy, and off-record politeness strategy. However, Sule tends to use a positive politeness strategy in interviewing his guest. The positive politeness strategy realized in the podcast were focusing attention notice, attend to hearer, exaggerate, intensify interest to hearer, use in- group identity markers, seek agreement, avoid disagreement, joke, being optimistic, giving or asking for specific reasons, give gifts to the hearer. The reason of using each strategy is considering the responses he accepted from the guests, the intimacy factor, and weighing the risks of each strategy.